The Effect Of Parents' Socioeconomic Status And Pocket Money Management On Financial Self-Efficacy Through Informal Economic Education At Sdn Inpress Karunrung - Uqbah Al Ansyari, Mas'ud; Hasbi, Hasbi (Cita konsultindo, 2024)
Socioeconomic status of parents, pocket money management, informal economic education, and financial self-efficacy. This study aims to determine the influence of parental socioeconomic status and pocket money management on parental involvement through Financial Self-Efficacy. The analysis technique in quantitative research is applied by data collection studies using numbers, statistical analysis that provides a general overview of the characteristics of each research variable. The data collection technique used in this study is a questionnaire or questionnaire with a closed questionnaire model. This study uses the population, namely the parents of students of SDN Inpress Karunrung. As for the sampling method, it uses the porpusive sampling technique. Purposive sampling is a sampling method that requires thought. Various criteria are used in sampling while utilizing this strategy. The sample in this study was 25 respondents. The results of the study were obtained as follows: 1). The socioeconomic status of parents (X1) has a direct effect on financial self-efficacy (Y). 2). The management of pocket money (X2) has a direct effect on financial self-efficacy (Y) 3). Informal economics education (Z) has a direct effect on financial self-efficacy (Y). 4). The socioeconomic status of parents (X1) has a direct effect on informal economic education (Z). 5). The management of pocket money (X2) has a direct effect on economic education (Z). 6). The socioeconomic status of parents (X1) has a direct effect on financial self-efficacy (Y) through economic education (Z). 7). The management of pocket money (X2) has a direct effect on financial self-efficacy (Y) through informal economic education (Z).